OP0320 Determinants of rituximab pharmacokinetics and clinical outcomes in patients with anca-associated vasculitis. (15th June 2017) - Cornec, D; Kabat, B; Mills, J; Cheu, M; Hummel, A; Schroeder, D; Cascino, M; Brunetta, P; Murray, D; Snyder, M; Fervenza, F; Hoffman, G; et al.
Abstract : Background: Response to rituximab (RTX) is variable in patients with ANCA-associated vasculitis (AAV), and predictors of treatment efficacy/relapse risk would be useful. Previous studies have shown that RTX pharmacokinetics (PK) is associated with treatment efficacy in patients with lymphoma. Objectives: To study the determinants of RTX PK in patients treated for AAV and its association with clinical outcomes. Methods: This study included 88 patients from the RTX in ANCA-Associated Vasculitis (RAVE) trial who received the full dose of RTX (4 weekly 375 mg/m 2 infusions) and had available serum samples. RTX was quantified using two different assays: a traditional ELISA and a recently developed mass spectrometry-based assay (referred to as miRAMM). We analyzed week (W)2, W4, W8, W16 and W24 serum levels and the trapezoidal area under the curve (AUC) integrating baseline, W2, W4, and W8 levels. We explored potential determinants of RTX PK using univariate and multivariate analysis, and analyzed the association of RTX PK with clinical outcomes: achievement of complete remission at 6 months (defined by a BVAS/WG score of 0 with no prednisone), time to relapse in patients who achieved complete remission, and B-cell depletion duration. Results: RTX quantifications using ELISA and miRAMM were highly correlated, but miRAMM measured consistently higher serum levels, suggesting its ability to detect total serum RTX (including free and complexed rituximab). RTX PK was highly variable between patients, with W2 levels ranging between 43 and 259 μg/mL and AUC ranging between 2, 668 and 17, 513 μg/mL by miRAMM. W2 RTX levels and AUC were significantly lower in males and in newly-diagnosed patients, and were negatively correlated with body surface area, baseline B-cell count, and BVAS/WG. In multivariate analyses, the main determinants of RTX PK were sex and new diagnosis. Patients with a new diagnosis had higher baseline B-cell counts and BVAS/WG. Patients reaching complete remission at month 6 had similar mean RTX levels compared to patients who did not reach complete remission (W2 level by miRAMM: 136±44 vs 139±46, p=0.76; AUC: 8420±2875 vs 8558±3452, p=0.85). Patients with higher RTX levels generally experienced longer B-cell depletion durations, but RTX levels at the different time-points and AUC were not associated with time to any relapse or time to severe relapse. Similar results were observed when using rituximab quantification by miRAMM and by ELISA. Conclusions: Despite a dosing protocol adjusted for body surface area, rituximab PK is highly variable between patients, its main determinants being sex and newly diagnosed disease. We did not observe an association between rituximab PK and clinical outcomes. Serum rituximab level monitoring does not seem clinically useful in this context. Disclosure of Interest: None declared